Digital Transformation in Teaching: Bridging the Gap Between Resource Utilization and Pedagogical Practices - Upadhayaya, Parshu Ram; Ghimire, Paras Mani; Sharma, Bishnu (Ganeshman Darpan, 2026)
This study explores the digital transformation of teaching with particularly focus on the resource utilization and practices within higher education. Drawing from a range of scholarly literature, the research examines how digital tools address critical gaps in digital pedagogy, particularly in Nepal’s educational landscape. Despite the growing emphasis on ICTs in education, teacher educators face challenges such as limited technological proficiency, insufficient training, and resistance to structured digital strategies. The study is grounded in the Technological Pedagogical Content Knowledge (TPACK) and Unified Theory of Acceptance and Use of Technology (UTAUT) frameworks, drawing on prior research that highlights the need for institutional support and training in digital adoption. A qualitative methods approach was employed through reflective notes and classroom observations. The research questions focus on assessing existing digital competencies, examining proficiency levels, and exploring integration practices in teaching learning strategies.